2006
DOI: 10.1590/s0102-86502006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arterial hypertension treated with losartan on skin healing in rats

Abstract: PURPOSE: To evaluate the role of Losartan in skin healing repair. METHODS: One hundred and eleven male Wistar rats were distributed into four groups, at random. Group I (n=31) underwent a laparotomy to induce hypertension by stenosis of the left renal artery, and 48 hours later it received Losartan (10 mg/Kg) daily. Group II (n=30) went through the same procedure and received isotonic saline solution. Group III (n=30) underwent a simulated laparotomy. Group IV (n=20) to confirm the induced hypertension method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…We also conducted a retrospective clinical study on the effect of antihypertensive drugs on outcomes of breast reconstruction and found that ARB use was significantly associated with an increased risk of surgical complications after breast reconstruction (17). The findings of our previous clinical study regarding the effect of ARB use on surgical complications in the clinical setting were consistent with those of previous studies using experimental models (13)(14)(15)(16)28,29), despite the discrepancy in the dose and administration period of ARBs; the dose of ARBs was higher in experimental models (29,30), and chronic use of ARBs was predominant in human subjects (17).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We also conducted a retrospective clinical study on the effect of antihypertensive drugs on outcomes of breast reconstruction and found that ARB use was significantly associated with an increased risk of surgical complications after breast reconstruction (17). The findings of our previous clinical study regarding the effect of ARB use on surgical complications in the clinical setting were consistent with those of previous studies using experimental models (13)(14)(15)(16)28,29), despite the discrepancy in the dose and administration period of ARBs; the dose of ARBs was higher in experimental models (29,30), and chronic use of ARBs was predominant in human subjects (17).…”
Section: Discussionsupporting
confidence: 81%
“…ARBs act by selectively blocking angiotensin II type 1 receptor (AT1R), and clinical evidence suggests that they have cardiovascular, cerebral, and renal protective effects (27). In contrast, several experimental studies have demonstrated that angiotensin II-AT1R signaling plays a crucial role in wound healing and angiogenesis (26), and inhibition of AT1R by ARBs can cause decreased wound healing by inhibiting re-epithelialization, dermal repair, and angiogenesis (16) and reduced wound tensile strength by inhibiting collagen synthesis and deposition (15,28). In addition, treatment with ARBs has been demonstrated to cause massive graft loss after meshed split-thickness skin grafting in a porcine full-thickness burn wound model (29).…”
Section: Discussionmentioning
confidence: 99%
“…After laparorrhaphy the animals were returned to their boxes where they were given water and food ad libitum until the date scheduled for hepatectomy. This method leads to hypertension as described in a previous study 13 . A week later, under new anesthesia, a new laparotomy was followed by partial hepatectomy, resection of the left lateral and median lobes.…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of type I collagen in Wistar rats on the fourth, seventh and fourteenth days after surgery for bowel suture, in the control group was 27.3%, 26.7% and 31.3%, respectively 18 .…”
mentioning
confidence: 89%
“…Biondo-Simões et al 16,18 observed progressive gain of collagen in the anastomosis area on the fourth, seventh and fourteenth days after surgery for bowel suture in Wistar rats in the control group. Tostes et al 17 measured the concentration of hydroxyproline in the abdominal wall of SHR rats subjected to laparotomy, obtaining the progressive concentration of hydroxyproline, which is a good marker of the amount of collagen in tissue 36 , on the seventh and fourteenth day after surgery.…”
mentioning
confidence: 99%